Everything you wanted to know about convict criminology but were too afraid to ask - Ross, Jeffrey Ian (Autonomie locali e servizi sociali, 2020)
This article provides a brief introduction to the field of Convict Criminology (CC). It tackles six main topics that would interest audiences unfamiliar with CC. These include: What is Convict Criminology? Who counts as a Convict Criminologist? What is the history of CC? What has CC accomplished? What have been the major criticisms of CC? and What has been CC’s response to these criticisms? The article concludes by both summarizing the contents of the piece and makes some suggestions for the future.